Economic Value of Food Commodities and Labor Shift due to Rice Field Conversion in Batu City, Indonesia - Susilo, Susilo (Journal of The Community Development in Asia, 2023)
Increasing tourist activities in Batu City makes agricultural land conversion unavoidable. This research aims to determining the lost economic value of food commodities due to converted agricultural land area and labor shift. The conversion area of agricultural land in all areas can be identified through Landsat image 8 ETM+ in 2017 and 2021. An overlay analysis using ArcGIS 10.2 software with 7 variables was then utilized to determine land capability and land suitability. Then, it was combined with the survey results of 334 land price points to determine the distribution of agricultural land prices in Batu City by using Kriging interpolation analysis. The results of the research show that the agricultural land area has decreased in the past 4 years by 169.96 Ha, with a lost economic value of approximately 5 billion Indonesian rupiah. The agricultural land price in Batu City is divided into 4 classifications. The results indicate that the agricultural land price is high, so it accelerates the agricultural land conversion. Therefore, the government should pay close attention to land conversion.